Ecological Change and Language Change - Handoko Handoko (Andalas International Journal of Socio-Humanities, 2020)
The current article discuss short description of language and ecology, or ecolingusitcs in regard to the language and social change. The article discuss the concept of ecolingustics and some approach to the study. Then, we discuss how the change of ecology and ecosystem affect the language, especially regarding language vitality. The paper also provide some examples of agricultural lexicon that rarely used due to the change of agricultural system. There some aspect that affect the language change, including language contact, environment change, language standardization, and the attitude of the speaker.